Carbohydrate intake and insulin requirement in children, adolescents and young adults with cystic fibrosis-related diabetes: A multicenter comparison to type 1 diabetes - Scheuing, Nicole; Thon, Angelika; Konrad, Katja; Bauer, Maria; Karsten, Claudia; Meissner, Thomas; Seufert, Jochen; Schoenau, Eckhard; Schöfl, Christof; Woelfle, Joachim; Holl, Reinhard W. (Clinical Nutrition, 2015)
In cystic fibrosis-related diabetes (CFRD), energy needs differ from type 1 (T1D) or type 2 diabetes, and endogenous insulin secretion is not totally absent. We analyzed whether daily carbohydrate intake, its diurnal distribution and insulin requirement per 11 g of carbohydrate differ between CFRD and T1D.Anonymized data of 223 CFRD and 36,780 T1D patients aged from 10 to <30 years from the multicenter diabetes registry DPV were studied. Carbohydrate intake and insulin requirement were analyzed using multivariable regression modeling with adjustment for age and sex. Moreover, carbohydrate intake was compared to the respective recommendations (CFRD: energy intake 130% of general population with 45% carbohydrates; T1D: carbohydrate intake 50% of total energy).After demographic adjustment, carbohydrate intake (238 ± 4 vs. 191 ± 1 g/d, p < 0.001) and meal-related insulin (0.52 ± 0.02 vs. 0.47 ± 0.004 IU/kg*d, p = 0.001) were higher in CFRD, whereas basal insulin (0.27 ± 0.01 vs. 0.38 ± 0.004 IU/kg*d, p < 0.001) and total insulin requirement per 11 g of carbohydrate (1.15 ± 0.06 vs. 1.70 ± 0.01 IU/d, p < 0.001) were lower compared to T1D. CFRD patients achieved 62% [Q1;Q3: 47; 77] of recommended carbohydrate intake and T1D patients 60% [51; 71] of age- and gender-specific recommended intake (p < 0.001). CFRD and T1D patients had a carbohydrate intake below healthy peers (79% [58; 100] and 62% [52; 74], p < 0.001). The circadian rhythm of insulin sensitivity persisted in CFRD and the diurnal distribution of carbohydrates was comparable between groups.In pediatric and young adult patients, carbohydrate intake and insulin requirement differ clearly between CFRD and T1D. However, both CFRD and T1D patients seem to restrict carbohydrates.
EVALuna2:1979